Evidence-based emergency care diagnostic testing and clinical decision rules - Pines, Jesse M. (Wiley, 2013)
"The purpose of this book is to present relevant questions on diagnostic testing that arise in everyday emergency medicine practice and to comment on the best available evidence"--Provided by publisher.